(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: Left displaced abomasum (LDA) is a common postparturient condition of high yielding dairy cattle. The diagnosis of LDA is challenging and has historically been based on findings that are not specific to the condition. The objective of the current study was to investigate the diagnostic performance of ultrasonography (USG) in the clinical management of dairy cows identified with left-sided ping sound postpartum. Materials and methods: Cows with reduced appetite postpartum and had audible left-sided ping sounds on abdominal auscultation were eligible to be prospectively recruited onto the study. The results of clinical findings and abdominal USG were recorded along with milk β-hydroxybutyrate levels, pH levels of abomaso/rumenocentesis samples, and findings on exploratory laparotomy. The diagnostic performance of USG and other clinical investigations was assessed by calculating the test sensitivity and specificity using exploratory laparotomy as a gold standard test. Results: A definitive diagnosis of LDA was made in 23 cows, 8 cows were diagnosed with peritonitis, and 4 cows with frothy tympany. The USG findings that were consistent with LDA were present in all cattle diagnosed with LDA at exploratory laparotomy. The USG findings over the past three intercostal space characteristics of LDA, however, were also present in five cases subsequently diagnosed with peritonitis and in all cases diagnosed with frothy tympany on exploratory laparotomy. The pH of abdomaso/rumenocentesis samples yielded the highest diagnostic accuracy (97.14%) as a single test in the current study. Conclusions: USG over the left abdominal wall despite being a highly sensitive test for the diagnosis of LDA has limitations as a diagnostic tool due to suboptimal specificity. Adv. Vet. Anim. Res., 7(2): 308-313, June 2020